Churchill's last stand : the struggle to unite Europe - Klos, Felix (London ; New York : I.B. Tauris & Co. Ltd., 2018)
After the Second World War, with much of Europe in ruins, the victorious Winston Churchill swore to build a peace across Europe that would last a generation. Fighting against the new 'Iron Curtain' which had fallen across the world, and battling the personal disappointment of losing the 1945 election in Britain, Churchill dedicated the rest of his life to forging a united Europe. This book, based in part on new evidence, reveals his vision: Britain as a leading member of the European family. Through Churchill's own private papers, Felix Klos unveils Churchill's personal battle to regain his place in world affairs, his confidential conversations with European leaders and the thinking and preparation behind some of his most powerful speeches. A beautifully written history of Europe after the war, and a new glimpse at one of its greatest statesmen.
'Something that will astonish you': Zurich: 19 September 1946 -- 'Vague and puzzling idealism': 1930-1940 -- Three days in June: indissoluble union, 1940 -- 'A good European': from Adana to Potsdam, 1940-1945 -- 'Let Europe arise!': Switzerland, September 1946 -- 'The big thing in a big way': Zurich, September 1946 -- 'The ideal should be EUROPE': Campaigning in Britain I, 1946-1947 -- 'We shall have done our best': campaigning in Britain II, 1947-1948 -- 'Here I am at home': the Congress of Europe, May 1948 -- 'Where are the Germans?': The Council of Europe, 1949-1951 -- 'A sad disillusionment': peacetime government, 1951-1952 -- Exactly what I suggested at Strasbourg': European defence, 1952-1955 -- 'My party was too strong for me': last thoughts, 1955-1965.
Includes bibliographical references (pages 265-307) and index.
Keywords: Churchill, Winston, -- 1874-1965.; Peace-building -- Europe -- History -- 20th century; Europe -- History -- 1945-; Great Britain -- Foreign relations -- Europe; Europe -- Foreign relations -- Great Britain